COMPATIBILITY OF CAMELS AS MEASUREMENTS INSTRUMENTS OF SHARIA BANK PERFORMANCE ON JUSTICE IN ISLAMIC PERSPECTIVES - Siti Asiam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research has the purpose to analyze the compatibility of CAMELS as measurement instruments of sharia banks performance on justice that is based on Islamic perspectives based on the theory of paired epistemology and through analysis of the materialistic aspect with the spiritualistic aspect by using a qualitative method and document studies. The result of this research concluded that the assessment components of CAMELS that is stated in Peraturan Bank Indonesia Nomor: 9/1/PBI/2007 and Surat Edaran Bank Indonesia No.9/24/DPbS do not fulfill the justice based on justice in paired epistemology theory. This is because there is not yet a formulated standard that is suitable for sharia banks. Key Words: CAMELS, Justice, Material, Spiritual, Paired Epistemology